ELECTRON GAS IN ASYMMETRIC BICONVEX THIN QUANTUM LENS: REALIZATION OF KOHN’S THEOREM - Hajrapetyan, D.B.; Petrosyan, L.S.; Kazaryan, E.M.; Sarkisyan, H.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2017)
The problem of electromagnetic absorption in the electronic gas, which is localized in asymmetric biconvex thin quantum lens, is discussed. It is shown, that in the case of thin lens, in the plane of quantum lens electron gas is localized in two-dimensional parabolic confining potential. Thus, in this system the conditions for the realization of the generalized Kohn’s theorem are satisfied.